Estimation of Particle Size and Band Gap of Zinc Oxide Nanoparticle Synthesized by Chemical Precipitation Method - Gautam, Surendra K.; Sapkota, Bibek; Bhujel, Arun; Bhattarai, Sitaram (Journal of Nepal Chemical Society, 2020)
Zinc oxide (ZnO) nanoparticles were synthesized by chemical precipitation method using 0.1M and 0.3M [Zn(NO3)2.6H2O] and Na2CO3 solutions. The particle size and band gap of ZnO nanoparticles were estimated and effect of concentration on it was investigated. The synthesized nanoparticles were characterized by X-ray diffraction (XRD), Transmission electron microscopy (TEM), Energy dispersive X-ray spectroscopy (EDX), Fourier transform infrared spectroscopy (FTIR) and UV-visible spectroscopy. The XRD result revealed that synthesized ZnO nanoparticles have pure hexagonal wurtzite structure and the particle size varies from 27.0 nm to 29.9 nm estimated by using Debye-Scherrer’s equation. The TEM image also projected the average particle size in the range of 20-30 nm and selected area electron diffraction (SAED) further verified the formation of hexagonal wurtzite structure. The FTIR result showed a broad absorption band related to Zn-O vibration band. The UV-visible absorption showed a red shift in the absorption edge with increasing concentration of Zn(NO3)2.6H2O solution. The sizes and band gaps of ZnO nanoparticles increased and decreased, respectively with increasing concentration of Zn(NO3)2.6H2O solution from 0.1M to 0.3M.